Screening of rice germplasm and validation of markers for high temperature stress tolerance using morphologic traits and molecular markers - Mohapatra, Sudipti; Barik, S R; Meher, J; Patra, B C; Pradhan, S K (ORYZA-An International Journal of Rice, 2018)
High temperature stress is one of the devastating abiotic stresses which severely affect yield in rice. The present investigation analyzes the genetic variability, heritability, genetic advance in yield related traits like panicle length, panicle neck length, panicle exsertion, spikelet fertility, thousand grain weight and days to 50% flowering of a set of genotypes under high temperature stress and normal condition and further validation of molecular markers linked to high temperature stress tolerance. The germplasm lines namely Annapurna, Wita-12, N22, CR 2599-2, Dular, IR83373-B-B-24-4, IR88836-4-1-3-2, IR88963-31-6-1-1-IRRI, IR 84887-B-157-38-1-1-3, IR84899- B-183-6-1-1-2 were identified as tolerant to high temperature stress. Molecular markers viz., RM547, RM212, RM566, RM127, RM225 and RM242 reported in mapping of high temperature stress tolerance were validated in these donor lines.